SLEEP DISORDERS IN EPILEPTIC PATIENTS - V. A. Karlov; O. S. Inozemtseva; G. B. Novoselova (Эпилепсия и пароксизмальные состояния)
Objective. To investigate the main features of sleep disorders in patients with three main forms of epilepsy and its impact on the quality of life. Materials and  methods. One hundred and fifty patients with different forms of epilepsy (including idiopathic, cryptogenic, and symptomatic) aged 17-64 years were enrolled. The following parameters were evaluated: presence  of sleep  disorders  (estimated  using  special questionnaires  developed  by the  Somnological  Center of the Ministry of Health of the Russian Federation), presence  of daytime sleepiness according to the Epworth scale, level of anxiety and depression according to the hospital scale (HADS), quality of life (analyzed using the QOLIE-89 questionnaire). Results.  Patients in all three groups experienced  daytime sleepiness, difficulty falling asleep and maintaining sleep at night, problems with final awakening. We found a reliable correlation between the daytime sleepiness at rest or during activities with the subjective sleep characteristics, difficulty falling asleep and maintaining sleep, level of anxiety, and the values from QOLIE-89 questionnaire (quality of life). Conclusion. Our findings demonstrate  the obligatory nature of the circadian rhythm  sleep  disorders  in all three  groups  of  epileptic  patients.  The differences  in the  subjective  sleep characteristics between the groups (depending on the form of epilepsy: symptomatic/cryptogenic and idiopathic) can be compared with the psychological characteristics of the patients with these forms of epilepsy.